In‐plane Epitaxy of Bi2S3 Nanowire Arrays for Ultrasensitive NIR Photodetectors. Issue 11 (22nd September 2020) - Xu, Xing; Fan, Chao; Wang, Yanguo; Qi, Zhuodong; Dai, Beibei; Jiang, Haotian; Wang, Shaowei; Zhang, Qinglin
Abstract : The direct growth of semiconductor nanowire (NW) arrays horizontally aligned on a substrate is critically important for the applications of NWs in electronic or optoelectronic devices at the circuit level. The strict requirement of lattice matching between a substrate and a material in the covalent epitaxy of crystals makes the wire arrays be grown on the substrates only with similar lattice parameters. Herein, a van der Waals epitaxy route is developed to realize the in‐plane growth of large‐scale Bi2 S3 NW arrays on mica with a large lattice mismatch. The orthorhombic Bi2 S3 NWs grow epitaxially with the axial direction of ⟨ 001 ⟩ Bi 2 S 3 along the six symmetric directions of the mica. Transmission electron microscope measurements show that the epitaxial relationships are [ 001 ] Bi 2 S 3 | | [ 100 ] mica and [ 3 2 ¯ 0 ] Bi 2 S 3 | | [ 010 ] mica along the length and width directions of the wires, respectively. More importantly, photodetectors based on Bi2 S3 NWs show a wide photoresponse spectrum range from 500 to 980 nm. A high responsivity (5233 A W −1 ) and a specific detectivity (1.8 × 10 12  Jones) are achieved under 830 nm light irradiation with ultralow intensity (64 nW cm −2 ). In addition, the photodetectors exhibit high stability with at least 48 day storage in ambient atmosphere or with 1000 times bending. Abstract : Herein, the in‐plane epitaxial growth of Bi2 S3 nanowire arrays on mica is demonstrated. Photodetectors based on Bi2 S3 nanowires show high responsivity and sensitivity under 830 nm light irradiation and a broad detection range, with high mechanical stability in air.